Online Marketplace's Role and Legal Responsibilities on 'Official Store' Restrictions To Implement Fair Competition Principle - Andyna Susiawati Achmad; Astrid Athina Indradewi (Universitas Airlangga, 2023)
In order to implement the idea of fair business competition, this article will analyze the function and legal obligations of online marketplaces in limiting commercial actors as 'official stores'. Normative juridical law research with statutory and conceptual techniques was used to create this study. According to the results, the distribution of commodities from producers to consumers has been altered by digital disruption. Currently, a number of online marketplace platforms offer 'official store' services to a small group of business players so they can expand their enterprises exclusively. Applying 'official stores' terms and conditions to business actors is prohibited by both Law No. 5 of 1999, which prohibits unfair business competition, and Government Regulation 29 of 2021, which relates to the implementation of the trade sector. Distributors and agents of associated producers will face unfair economic rivalry as a result of producers entering the online market as 'official stores'. Producers are prohibited from selling their products in retail settings, whether offline or online, in accordance with the relevant legislation. The findings of this study should benefit the parties involved in the online marketplace by fostering fair commercial competitiveness.